Efficacy of Acacia senegal for Stoma Care in Children with Colostomy - Hosseinpour, Mehrdad; Fazeli, Ali; Agabeigi, Masoome (European Journal of Pediatric Surgery, 2012)
Introduction The creation of a stoma on the abdomen and the need for appliance on the peristomal skin make this region vulnerable to inflammatory skin disorders .In this study, we introduce a novel protection with Acacia senegal and compare the protective effects of this barrier with zinc sulfate ointment.Methods and Materials To examine the effect of protective interventions, a prospective, controlled, clinical study was conducted. Participants were all infants consecutively admitted to the pediatric surgery unit of the study hospitals for elective surgery of colostomy creation. After laparotomy and double barrel colostomy creation, patients were randomly assigned to use one barrier (gum acacia or zinc sulfate ointment) for 4 weeks.Results In this study, a total of 60 infants (30 as case and 30 as control) were evaluated. Results showed that there was a statistically significant difference in peristomal skin inflammation rate in groups; infants who had Acacia senegal barrier showed lower and less sever inflammation rates (p = 0.05).Conclusion Compared with zinc oxide, we found a lower rate of dermatitis in the Acacia group.
Keywords: Acacia senegal; stoma care; peristomal dermatitis